A review on the role of CASC11 in cancers - Ghafouri-Fard, Soudeh; Harsij, Atefeh; Hussen, Bashdar Mahmud; Taheri, Mohammad; Sharifi, Guive (Frontiers in Cell and Developmental Biology, 2023)
The long non-coding RNA (lncRNA) cancer susceptibility 11 (CASC11) is a newly identified lncRNA located on chromosome 8q24.21. The expression of lncRNA CASC11 has been found to be elevated in different cancer types and the prognosis of the tumor is inversely correlated with the high CASC11 expression. Moreover, lncRNA CASC11 has an oncogenic function in cancers. The biological characteristics of the tumors, such as proliferation, migration, invasion, autophagy, and apoptosis can be controlled by this lncRNA. In addition to interacting with miRNAs, proteins, transcription factors, and other molecules, the lncRNA CASC11 modulates signaling pathways including Wnt/β-catenin and epithelial-mesenchymal transition. In this review, we have summarized studies on the role of lncRNA CASC11 in the carcinogenesis from cell lines, in vivo, and clinical perspectives.